DOCTAR - Krüger, Frank; Dahm, Torsten; Dias, Nuno A.; Matias, Luis; Silveira, Graça; Kriegerowski, Marius; Bülow, joachim (GFZ Data Services, 2011)
Abstract We installed two seismological broadband arrays on the volcanic oceanic island of Madeira and in western Portugal on continental crust for a comparison and combination with a deep ocean broadband array installed for seismicity analysis and structure imaging of the oceanic plate environment around the Gloria fault in the Northeast Atlantic with broadband arrays. The data of the deep ocean array are published separately. Waveform data are available from the GEOFON data centre, under network code Y7 under CC-BY 4.0 license.